Analisis Manajemen Layanan ELLS Universitas Amikom Purwokerto Menggunakan Framework ITIL V3 - Amanda Ayu Novitasari; Ito Setiawan; Mauly Chandra Gumilang; Zanela Anania Syafikah; Zuhriyatul Lubna (Switch : Jurnal Sains dan Teknologi Informasi, 2024)
In the digital era, the utilization of information technology has become a primary need to support various aspects of education. One of the innovations implemented in educational institutions is the use of e-learning platforms, which allow learners to study flexibly without being hindered by distance and time. Universitas Amikom Purwokerto has developed the E-Learning Support System (ELLS) website as an online learning tool accessible by students and lecturers. This study aims to analyze the service management of ELLS using the ITIL V3 framework, which provides a structured guide in managing and optimizing services to better meet user needs in a sustainable manner. The methodology used includes observation, interviews, and surveys distributed to service users. The results show that the implementation of ITIL V3 can improve service effectiveness, reduce the risk of disruptions, and provide a positive experience for users. This research is expected to provide recommendations for improving e-learning service management at Universitas Amikom Purwokerto and serve as a reference for other educational institutions looking to enhance the quality of their services.